Mucosal immunity and vaccines against viral infections - S. S. Zainutdinov; G. F. Sivolobova; V. B. Loktev; G. V. Kochneva (Вопросы вирусологии, 2022)
Mucosal immunity is realized through a structural and functional system called mucose-associated lymphoid tissue (MALT). MALT is subdivided into parts (clusters) depending on their anatomical location, but they all have a similar structure: mucus layer, epithelial tissue, lamina propria and lymphoid follicles. Plasma cells of MALT produce a unique type of immunoglobulins, IgA, which have the ability to polymerize. In mucosal immunization, the predominant form of IgA is a secretory dimer, sIgA, which is concentrated in large quantities in the mucosa. Mucosal IgA acts as a first line of defense and neutralizes viruses efficiently at the portal of entry, preventing infection of epithelial cells and generalization of infection. To date, several mucosal antiviral vaccines have been licensed, which include attenuated strains of the corresponding viruses: poliomyelitis, influenza, and rotavirus. Despite the tremendous success of these vaccines, in particular, in the eradication of poliomyelitis, significant disadvantages of using attenuated viral strains in their composition are the risk of reactogenicity and the possibility of reversion to a virulent strain during vaccination. Nevertheless, it is mucosal vaccination, which mimics a natural infection, is able to induce a fast and effective immune response and thus help prevent and possibly stop outbreaks of many viral infections. Currently, a number of intranasal vaccines based on a new vector approach are successfully undergoing clinical trials. In these vaccines, the safe viral vectors are used to deliver protectively significant immunogens of pathogenic viruses. The most tested vector for intranasal vaccines is adenovirus, and the most significant immunogen is SARSCoV-2 S protein. Mucosal vector vaccines against human respiratory syncytial virus and human immunodeficiency virus type 1 based on Sendai virus, which is able to replicate asymptomatically in cells of bronchial epithelium, are also being investigated.